Restricting Diversity to Promote Democracy: Community Literacies and Playing Across Spaces - Owen Samantha (Cultural Science)
In 2018 a teacher in a Montessori school captured on camera two children in her special education classroom using a touchscreen tablet to interact. To her it was significant: these pre-verbal children had found a way to independently share aspects of their lives. In 1965 a Nigerian mother commented that volunteering on a care rota in a playgroup in a housing estate in west London gave her the confidence to greet her neighbours when she saw them on the street. To Ilys Booker, the community development worker assigned to the area, this was also a marker of significant change and an indication of success. Using these two instances as starting points, this article explores the links between play/space/city and literacy/civic/citizenship by drawing together two case studies: Notting Dale, London, 1964–1969 and River Montessori School, Australia, 2018. In both case studies, the institutional concern is over how the target groups are educated to become literate as citizens, with a focus on exhibited values and virtues. Working from a historical perspective this paper asks: what are the historical conditions which determine our current understandings of participatory culture? How do these enable and/or limit the possibilities of Open Literacy? How do communities form in a liberal democracy and what roles do institutions play?